2020
DOI: 10.3390/molecules25122886
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Hypertension and Plasma Glucose Modulate the Vasoactive Effects of Nitroso-Sulfide Coupled Signaling in Human Intrarenal Arteries

Abstract: We have investigated the vasoactive effects of the coupled nitro-sulfide signaling pathway in lobar arteries (LAs) isolated from the nephrectomized kidneys of cancer patients: normotensive patients (NT) and patients with arterial hypertension (AH). LAs of patients with AH revealed endothelial dysfunction, which was associated with an increased response to the exogenous NO donor, nitrosoglutathione (GSNO). The interaction of GSNO with the H2S donor triggered a specific vasoactive response. Unlike in normotensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
(55 reference statements)
2
6
0
Order By: Relevance
“…Our previous studies showed an obvious interaction between two important vasoregulatory molecules, NO and H 2 S, and their pathways and suggested the existence of a coupled nitroso-sulfide signaling pathway [24,25]. Herein, we confirmed that the heterogeneity of specific nitroso-sulfide vasoactive signaling exists depending on the occurrence of different pathological stages, e.g., hypertension or increased plasma glucose levels [26]. Recently, in a non-obese rat model of metabolic syndrome (HTG rats), we confirmed a significantly higher expression of CSE in the arterial wall of the TA compared to control rats, and that the endogenous H 2 S participated in the inhibition of NO-mediated vasorelaxation [27].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our previous studies showed an obvious interaction between two important vasoregulatory molecules, NO and H 2 S, and their pathways and suggested the existence of a coupled nitroso-sulfide signaling pathway [24,25]. Herein, we confirmed that the heterogeneity of specific nitroso-sulfide vasoactive signaling exists depending on the occurrence of different pathological stages, e.g., hypertension or increased plasma glucose levels [26]. Recently, in a non-obese rat model of metabolic syndrome (HTG rats), we confirmed a significantly higher expression of CSE in the arterial wall of the TA compared to control rats, and that the endogenous H 2 S participated in the inhibition of NO-mediated vasorelaxation [27].…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, it seems that there was a higher expression of CBS than in CSE in the aortic arterial wall (Figure 10). We previously found similar results in human intrarenal arteries, where we did not record gene expression of CSE in the arterial wall, but the mRNA of CBS was detectable [26]. This finding could explain the evidence that the acute inhibition of CSE revealed weaker vasoactive effects than the H 2 S scavenger, and BSC could eliminate H 2 S also produced by CSE-independent sources, including CBS.…”
Section: Discussionsupporting
confidence: 74%
“…Several reports propose that the products of H 2 S-NO interaction, particularly SSNO − , play an important role in the regulation of BP [ 9 , 17 , 18 , 37 ]. Therefore, we have studied the effect of SSNO − -mix on BP.…”
Section: Discussionmentioning
confidence: 99%
“…Since endogenously produced gasotransmitters, hydrogen sulfide (H 2 S) and nitric oxide (NO), and the products of H 2 S/NO interactions (referred as SSNO − -mix) influence various physiological processes, particularly regulate blood pressure (BP) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], it was of interest to study the effects of H 2 S and SSNO − -mix on 35 HPs and subsequently compare the selected cross-relationships of the HPs and their non-hysteresis/hysteresis “patterns” to the published data for NO-donor S-nitrosoglutathione (GSNO) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of the cross-talk between EDRFs and EDCFs results in the alteration of normal physiological processes carried out by the endothelium, including reduction of its anticoagulant and antithrombotic properties, acceleration of vascular growth and remodeling, and impairment of endothelium-dependent vasorelaxation, i.e., in endothelial dysfunction [ 6 ]. Endothelial dysfunction was documented not only in animal models, but also in patients with arterial hypertension [ 166 ]. Prevention of endothelial dysfunction represents an important step in the prevention or mitigation of CVDs and hypertension.…”
Section: Cellular and Molecular Mechanisms Of Ec And Tx Action Relmentioning
confidence: 99%